Do computer-mediated communication skill, knowledge and motivation mediate the relationships between personality traits and attitude toward Facebook?. (May 2017) - Chua, Yan Piaw; Chua, Yee Pei
Abstract: Social networking sites (SNSs) are observed to have both positive and negative effects on users' social, emotional, and cognitive development, which would further influence their self-esteem and well-being. Hence, understanding the behavior of users in online social networking is important. The present study investigates the causal relationships between Facebook users' personal factors and attitude toward Facebook. The study hypothesizes that personality traits would be significantly associated with attitude toward Facebook and that the association would be mediated by computer-mediated communication (CMC) skill, CMC knowledge and CMC motivation. The participants in this study are 327 school teenagers. The results indicate that participants who are extraverted and open to experience possess a positive attitude toward Facebook. Conscientious participants possess a negative attitude toward Facebook; however, for participants who are neurotics or who are agreeable, their attitude toward Facebook is not influenced by their personalities. An important finding of this study is that the three CMC competence components are mediators that either enhance or reduce the strengths of the causal relationships between four personality traits – neuroticism, extraversion, conscientiousness and openness to experience – and participants' attitude toward Facebook. Highlights: We investigate relationships between personality traits and attitude toward Facebook. Four of the Big Five personality traits significantly related to the attitude. The traits are neuroticism, extraversion, conscientiousness and openness. CMC competence mediates the strengths of the relationships.